ADVOCACY APPROACH WITH OPEN-ENDED PROBLEMS TO MATHEMATICAL CREATIVE THINKING ABILITY - Ibrahim Ibrahim; Sri Adi Widodo (Jurnal Infinity, 2020)
The purpose of this study is to find out the increase in students' ability to think creatively in advocacy learning by using open-ended problems. This type of research is an experiment with nonequivalent control group design. The sample in this study were 72 students taken using random sampling techniques. The variables in this study are learning models, mathematical creative thinking abilities, and general mathematics abilities. The instruments used in this study were creative thinking tests and general mathematics tests. Data analysis techniques used in this study are statistical inference using the Mann-Whitney test and one-way ANOVA. The results showed that students who were treated with an advocacy approach by presenting open-ended problems improved their mathematical creative thinking abilities better when compared with conventional learning.